ACTR-12. PHASE 2 STUDY OF DIANHYDROGALACTITOL (VAL-083) IN PATIENTS WITH MGMT-UNMETHYLATED, BEVACIZUMAB-NAÏVE GLIOBLASTOMA IN THE RECURRENT AND ADJUVANT SETTING. (11th November 2019) - O'Brien, Barbara; Penas-Prado, Marta; Kamiya, Carolos; Pei Weathers, Shiao-; Yung, Alfred; Loghin, Monica; Harrison, Rebecca; Bacha, Jeffrey; Brown, Dennis; Johnson, Gregory; Langlands, John; Schwartz, Richard; et al.
Abstract: Current standard-of-care for glioblastoma (GBM) includes surgery followed by concurrent therapy with radiation and temozolomide (TMZ) followed by adjuvant TMZ (days 1–5 every 28 days. Almost all GBM patients experience recurrent/progressive disease, with a median survival after recurrence of 3–9 months. Second-line treatment for recurrent GBM with bevacizumab (BEV) has not improved survival, and effective therapies for GBM are lacking. Unmethylated promoter for O 6 -methylguanine-DNA-methyltransferase (MGMT) is a validated biomarker for TMZ-resistance and is correlated with poor patient prognosis. VAL-083 is a bi-functional DNA-targeting agent which rapidly induces interstrand DNA cross-links at N 7 -guanine, induces double-strand breaks and acts independent of MGMT DNA repair. The current ongoing trial is a biomarker-driven Phase 2 study in MGMT-unmethylated BEV-naïve adult GBM. The primary objective of this study is to determine the effect of VAL-083 on median overall survival (mOS) for MGMT-unmethylated GBM patients compared to historical control. Secondary efficacy endpoints include progression-free survival (PFS), overall response rate (ORR), duration of response (DOR), and quality-of-life. Thirty-five (35) subjects with recurrent GBM have received 40 mg/m 2 /day VAL-083 on days 1, 2, 3 of a 21-day cycle as the starting dose. Myelosuppression is the most common adverse event and a higher potential for this toxicity correlated with those patients who received a higher number of cycles of prior TMZ maintenance therapy, (>5 cycles vs. ≤5 cycles, p< 0.05). To minimize the potential for hematological toxicity in rGBM, subsequent subjects initiated treatment at 30 mg/m 2 /d VAL-083 x 3 consecutive days every 21 days. In addition, since TMZ is of limited value in the MGMT-unmethylated setting, a second arm in newly diagnosed GBM has been included to explore whether substituting TMZ with VAL-083 offers clinical benefit and extends the time to recurrence. Enrollment, safety data and study updates will be presented at the meeting. Clinicaltrials.gov identifier: NCT02717962.